Properties of a certain product of submodules - Heidari, S.; Nikandish, R.; Nikmehr, M.J. (Український математичний журнал, 2011)
Let R be a commutative ring with identity, M an R-module and K1, . . . , Kn submodules of M. In this article, we construct an algebraic object, called product of K1, . . . , Kn. We equipped this structure with appropriate operations to get an R(M)-module. It is shown that R(M)-module Mⁿ = M . . . M and R-module M inherit some of the most important properties of each other. For example, we show that M is a projective (flat) R-module if and only if Mⁿ is a projective (flat) R(M)-module